External prescription circulation and chronic medication refills via internet hospital: a real-world study of patient characteristics in eastern China - Ying Zhang; Zhe Feng; En-feng Li; Jinqiu Hu (Frontiers in Public Health, 2026)
Background The COVID-19 pandemic has accelerated the adoption of internet-based care and electronic prescription systems, yet real-world evidence describing patient characteristics and usage patterns for hospital-led external prescription circulation and chronic medication refill services remains limited. Such evidence is urgently needed to guide service optimization and health equity in digital chronic disease management. Methods A single-center, retrospective, real-world study was conducted at a district-level hospital in eastern China. Data were collected over 65 days (January 23 to March 28, 2026), including 17,528 online chronic medication refill visits and 172,232 offline outpatient encounters. Patient demographics, temporal usage patterns, and prescription profiles were analyzed. Group comparisons were performed using chi-square tests, independent-samples t -tests, and effect-size statistics. A multivariable Generalized Estimating Equation (GEE) model was performed to identify independent predictors of evening service utilization. To quantify the macro-level impact of the Spring Festival on daily prescription volume, we additionally performed a negative binomial interrupted time series analysis adjusting for day-of-week and secular trend. Results The online patient cohort was characterized by an older demographic (mean age 55.0 years), with 84.85% aged ≥40 years. Distinct stratification was observed internally: older patients favored morning usage (08:00–10:00), whereas younger patients peaked in the evening (18:00–20:00; Cramér’s V = 0.165, p < 0.001). Cardiovascular drugs predominated among older patients, while younger patients used more Chinese patent medicines, digestive agents, and anti-inflammatory drugs (Cramér’s V = 0.167, p < 0.001). Multivariable GEE analysis identified older age (≥40 years) (Wald χ 2 = 158.787, p < 0.001), male gender (Wald χ 2 = 10.845, p = 0.001), the Spring Festival period (Wald χ 2 = 23.346, p < 0.001), and chronic disease type (Wald χ 2 = 6.041, p = 0.014) as independent predictors for evening use. Conclusion Hospital-based internet prescription refill services effectively target middle-aged and older patients with chronic conditions and demonstrate strong age-related differences in timing and medication needs. These findings support stratified, user-centered digital health design rather than one-size-fits-all models. Wider implementation can improve equitable access to chronic medications, optimize resource allocation, and strengthen chronic disease care in the digital health era.